IDEOLOGI PASAR, EROTISASI, DAN DOMINASI PATRIARKI TARIAN JOGED BUMBUNG DALAM RUANG KOMODIFIKASI PERTUNJUKAN SENI DI BALI TAHUN 2022 (Jurnal Nawala Politika, 2023)
ABSTRACT The aim of this study is to determine the commodification of Joged Bumbung dance toward eroticism, market onslaught, and patriarchal culture by using the invention of tradition theory proposed by Hobsbawm (2003). The study is using qualitative research methods, therefore the interview is conducted through some informants who work as the head of the Joged Bumbung studio and some dancers of Joged Bumbung. The results of this study are first, the Joged Bumbung performance has been modified due to demands from market ideology. Second, there are several combinations performed by the studio and the dancers of Joged Bumbung in gamelan and movement by mixing with national and pop arts. Third, the emersion of female pengibing phenomenon as the market control and patriarchal domination. Fourth, there are differences in the management system of the studio and seka in the job security guarantee for the Joged Bumbung dancers.